2019
DOI: 10.1097/rlu.0000000000002870
|View full text |Cite
|
Sign up to set email alerts
|

68Ga-PMSA Uptake in the Lung

Abstract: 68Ga-PSMA is a promising tracer for both primary staging and detection of biochemical recurrence in prostate cancer. PSMA is also expressed in the neovascular endothelium of various solid malignancies possibly due to tumor-associated angiogenic factors and endothelial cell sprouting. We report a case of a 73-year-old man of prostate cancer with rising prostate-specific antigen levels. 68Ga-PSMA PET/CT was performed, which showed a focal lung lesion, with subsequent histological confirmation of adenocarcinoma o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 9 publications
2
1
0
Order By: Relevance
“…3,4 Conversely from [ 18 F]F-FDG, PSMA radioligands do not have uptake in the healthy brain parenchyma and might play a role in the study of malignancies that metastasize in this district, increasing the accuracy in the staging or restaging compared with the conventional imaging and [ 18 F]F-FDG PET/CT. 3,[5][6][7] As we reported in this case, recent articles described abnormal uptake of PSMA-targeting radiopharmaceuticals in the setting of primary lung tumors [8][9][10] ; furthermore, a recent study observed that PSMA expression in the vasculature of primary lung carcinomas has been associated with faster metastatic dissemination to the brain. 11 To the best of our knowledge, this is the first report of accidental finding of brain metastases from lung adenocarcinoma with [ 18 F]F-PSMA-1007 PET/CT.…”
supporting
confidence: 68%
“…3,4 Conversely from [ 18 F]F-FDG, PSMA radioligands do not have uptake in the healthy brain parenchyma and might play a role in the study of malignancies that metastasize in this district, increasing the accuracy in the staging or restaging compared with the conventional imaging and [ 18 F]F-FDG PET/CT. 3,[5][6][7] As we reported in this case, recent articles described abnormal uptake of PSMA-targeting radiopharmaceuticals in the setting of primary lung tumors [8][9][10] ; furthermore, a recent study observed that PSMA expression in the vasculature of primary lung carcinomas has been associated with faster metastatic dissemination to the brain. 11 To the best of our knowledge, this is the first report of accidental finding of brain metastases from lung adenocarcinoma with [ 18 F]F-PSMA-1007 PET/CT.…”
supporting
confidence: 68%
“…Several authors reported an [ 68 Ga]Ga-PSMA-11 uptake in lung adenocarcinoma [4,5]. We showed an increased PSMA ligand uptake in 11 R section lymph node.…”
supporting
confidence: 60%
“…68 Ga-PSMA is a promising tracer for both staging and detection of recurrence in prostate cancer 1 . 68 Ga-PSMA uptake has been reported in other solid malignant tumors including lung cancer, hepatocellular carcinoma, and renal cell carcinoma 2–4 . PSMA plays a major role in regulating angiogenesis and is expressed in the endothelium of tumor-associated neovasculature in these solid malignancies possibly due to tumor-derived angiogenic factors and endothelial cell sprouting 5,6 .…”
mentioning
confidence: 99%